Durability of engineered cementitious composite exposed to acid mine drainage. (April 2020) - Wu, Hao-Liang; Zhang, Duo; Du, Yan-Jun; Li, Victor C.
Abstract: Acid mine drainage (AMD) is detrimental to concrete cut-off walls due to acid and sulfate attacks. As a recently developed fiber reinforced cement-based composite with high tensile ductility and intrinsically tight crack width, Engineered Cementitious Composites (ECC, also known as Strain-Hardening Cementitious Composites, or SHCC) has potential advantages in resisting transport of water and contaminant if applied to the mine cutoff walls. The durability of ECC exposed to AMD, however, has not been previously studied, and is the main objective of this research. Mechanical properties of ECC exposed to AMD wet-dry cycles were investigated. In addition, MgO was added in ECC to improve self-healing performance. It was found that AMD wet-dry cycles coarsened pore structure and led to ECC's mass loss and compressive strength reduction. The AMD exposure also reduced ECC's first cracking strength, ultimate tensile strength and tensile strain capacity by 23.7%, 17.8% and 36.5%, respectively. Addition of MgO was found effective in enhancing ECC's resistance to AMD attack, by moderating the reductions in compressive strength, tensile ductility and mass loss. Further, the addition of MgO densified ECC's microstructure and improved self-healing behavior. We conclude that ECC containing 6% MgO retains the desirable tensile ductility and possesses acceptable durability against AMD for cutoff wall applications at mining sites.